Poetry in the Field: An Interview with Maghiel van Crevel. (2nd January 2019) - Stalling, Jonathan
Abstract : Jonathan Stalling and Maghiel van Crevel talk about the "wild and crazy" mainland Chinese poetry scene, insiders and outsiders and shifting positions, learning Chinese over and over again, (not) being a Sinologist, (new) area studies and the disciplines, and literary anthropology.